Anti-Inflammatory Effect of Liverwort (Marchantia polymorpha L.) and Racomitrium Moss (Racomitrium canescens (Hedw.) Brid.) Growing in Korea - So-Yeon Kim; Minji Hong; Tae-Hee Kim; Ki Yeon Lee; Se Jin Park; Sun Hee Hong; Kandhasamy Sowndhararajan; Songmun Kim (Plants, 2021)
Bryophytes contain a variety of bioactive metabolites, but studies about the anti-inflammatory effect of bryophytes are meager. Therefore, the present study aimed to compare the anti-inflammatory effect of methanol extract of Marchantia polymorpha L. (liverwort) and Racomitrium canescens (Racomitrium moss) in lipopolysaccharide (LPS)-induced HaCaT cells. To evaluate the anti-inflammatory effect of liverwort and Racomitrium moss, the levels of nitric oxide (NO) production and the mRNA expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) and tumor necrosis factor-α (TNF-α), and interleukin (IL)-6 and IL-1β in LPS-induced HaCaT cells were measured. The methanol extract of liverwort and Racomitrium moss significantly decreased LPS-induced NO production in HaCaT cells. When compared with Racomitrium moss extract, pre-treatment with methanol extract of liverwort markedly inhibited the expression of iNOS, COX-2, IL-6, and IL-1β at the concentration of 100 µg/mL with the exception of TNF-α. Further, liverwort extract markedly attenuated the production of TNF-α, IL-6, and IL-1β in the culture medium. In addition, ethyl acetate and butanol fractions obtained from the methanol extract of liverwort showed remarkable inhibitory activity against the production of NO in LPS-stimulated HaCaT cells. The LC-MS data revealed the presence of bisbibenzyl types of bioactive components in the methanol extract of liverwort. These data demonstrate that liverwort extract exhibits effective inhibitory activity against the production of inflammatory mediators in LPS-induced HaCaT cells and may be useful for the treatment of inflammation-mediated diseases.